Role of affect and task category-knowledge sharing tools fit on behavioural intention to use KS tools among knowledge workers - Lee, Angela Siew Hoong * (2015)
Knowledge sharing is an essential practice by organizations of the 21st century. To leverage on knowledge sharing activities and cultivate a knowledge based ecosystem, organizations have invested and deployed many types of Knowledge Sharing tools (KS tools). KS tools allow knowledge workers to share and use knowledge in organizations. The low usage of KS tools justify the need to study the usage and also the intention to use these tools in organizations particularly among knowledge workers. In addition, the decline of Knowledge Economy Index (KEI) and Knowledge Index (KI) for Malaysia showed that knowledge sharing and knowledge contribution in education, innovation, and ICT are deteriorating. The need to investigate knowledge workers' intention to use knowledge sharing tools to support knowledge practices seems a reasonable research goal. In this research, the focus is on the behavioral intention of knowledge workers to use KS tools among knowledge workers in Multimedia Super Corridor (MSC) status organizations. MSC-status organizations play a key role that contributes to the national KEI and KI for Malaysia. The main objective of this study is to identify factors that influence the intention to use KS tools among knowledge workers. In an attempt to provide answers to the research objective, Affective Technology Acceptance Model (A.T.A Model) is developed to examine the antecedents that influence the attitude and behavioral intention of the knowledge workers to use KS tools in their day-to-day tasks. The A.T.A Model integrates Technology Acceptance Model with Task-Technology Fit to examine the acceptance of technology by hypothesize fit between Task Category and KS tools to Behavioral Intention to use KS tools. The proposed research model also includes the role of affect drawing from theories by Russell’s Circumplex of Affect and Watson, Clark and Tellegen’s Consensual Model of Affect into the propose model. The A.T.A model also considers organizational factors and motivational factors that influence the Behavioral Intention to use KS tools among knowledge workers. Quantitative method using survey approach is adopted to collect data from respondents. The proposed A.T.A model is empirically examined using two hundred ninety five (295) respondents who comprised of knowledge workers from a sampling frame of two thousand five hundred and five (2505) knowledge workers in twenty-three (23) MSC-status organizations that participated in this research. The outcomes of the analysis support the overall structure of the model whereby sixteen (16) of the twenty two (22) hypothesis are supported. The Behavioral Intention to use KS tools is supported and explained by knowledge workers' Attitude, Task-Category and KS tools fit, Positive Affect and Trust. In this research, Attitude has the highest impact on Behavioral Intention, followed by Task Category-KS tools fit, Positive Affect and Trust. On the other hand, Negative Affect influences Behavioral Intention knowledge workers for three (3) different points in time only ("At the Moment", "Past Few Days", and "Past Few Weeks"). However, Extrinsic and Intrinsic Rewards are found to have no influence on Behavioral Intention to use KS tools. The findings highlighted that change in Positive Affect is able to create a positive impact in Behavioral Intention of knowledge workers to use KS tools besides Attitude and TCK fit. The findings highlighted that Positive Affect has an influence on Perceived Usefulness, but Negative Affect has no influence on it. However, both Positive and Negative Affect have an influence on Perceived Ease of Use. The results also found that Task Category KS tools fit influences Behavioral Intention significantly. This is consistent with past research, which claimed that integrating Task Category-KS tools fit to acceptance model is able to provide better explanation on the intention of individuals to use KS tools. On the contrary, this research found Extrinsic and Intrinsic Rewards, and Management Support have no significant relationship with Behavioral Intention to used KS tools in the proposed A.T.A model. Overall, the results of this study contribute to the literature of technology acceptance by shedding light on the behavioral intention to use KS tools among knowledge workers.